The mita of Chachapoyas in the year 1586 - Ruiz Estrada, Arturo (2011)
We present the mita system imposed by Spanish colonial power in the city of Chachapoyas in Peru’s Amazonas region, Peru. The study of the analysis in a document dated 1586 by which records the number of Indians scattered Spanish residents in the region of Chachapoyas. It is noted that the results of those deals were social implications and economic impact to the present.